Cystic Adenomatoid Odontogenic Tumor - Sonal Grover; Ahmed Mujib Bangalore Rahim; Nithin Kavassery Parakkat; Shekhar Kapoor; Kumud Mittal; Bhushan Sharma; Anil Bangalore Shivappa (Case Reports in Dentistry)
Adenomatoid Odontogenic Tumor (AOT) is a well-established benign epithelial lesion of odontogenic origin. Rightfully called “the master of disguise,” this lesion has been known for its varied clinical and histoarchitectural patterns. Not only does AOT predominantly present radiologically as a unilocular cystic lesion enclosing the unerupted tooth (which is commonly mistaken as a dentigerous cyst) but the lesion also presents rarely with a cystic component histopathologically. We present one such unusual case of cystic AOT associated with an impacted canine, mimicking a dentigerous cyst. The present case aims to highlight the difference between cystic AOT and dentigerous cyst radiographically. The exact histogenesis of AOT and its variants still remains obscure. An attempt has been made to hypothesize the new school of thought regarding the origin of AOT.